(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Throughout the world multi-drug resistant hospital acquired infections (HAI) are one of the leading causes of deaths and morbidity amongst hospitalized patients. Objective: The aim of study was to identify prevalence and variations of predominant microorganisms and their drug sensitivity and resistance pattern in a tertiary care public hospital, Dhaka, Bangladesh. Methodology: The study was conducted in Intensive Care Unit (ICU), High Dependency Unit (HDU), Post-operative ward and general wards of a tertiary care publicNeuro- hospital in Dhaka during 1st January, 2017 to 31st December, 2018. Patients admitted in any of the four units (ICU, HDU, Post-operative and general wards) of the hospital who were clinically suspected of having acquired any infection after 48 hours of admission to the ICUs were included. Depending on the clinical suspicion laboratory samples were collected from the patients. Samples were subjected to the testing and antibiotic sensitivity. Results: A total number of total 1672 samples from these patients yielded clinically relevant microorganisms. Of these samples, 273 were respiratory specimens were tracheal aspirate; 537 were urine; 377 were blood; 396 were cerebrospinal fluids; and 82 were other clinical samples. More than two-third samples were growth negative (71.4%) and only one-thirdsamples (28.6%) were growth positive. Maximum growth negative in blood samples and about half of samples of urine and tracheal aspirates were growth negative. About 80% were Gram-negative bacteria like Escherichia coli, Pseudomonas spp., Klebsiella whereas gram-positive organisms were about 20%. Most of the pathogens were Multi-drug resistance. Conclusion: Among HAIs Multidrug-resistant Gram-negative bacteria are the main challenge. Regular updating resistance of microbial are needed to develop antibiotic guideline to combat these infections and reduce morbidity and mortality. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 82-86